Semillas de Mammea americana L. en el control in vitro de garrapatas - García Araque, Jailinne Anavela (2025)
The objective of the study was to evaluate the effect of Mammea americana L. seed extract on the in vitro control of ticks. To achieve this, 320 ticks (Rhipicephalus microplus) were distributed across four treatments: a control group (T0) and three concentrations of aqueous extract from yellow mamey at 2.53% (T1), 5.03% (T2), and 6.43% (T3), expressed as total phenol concentration. Each treatment was replicated four times with 20 ticks per replicate. The Shapiro-Wilks test was used to verify data normality. The effects of the treatments were determined using Analysis of Variance (ANOVA) and its non-parametric equivalent (Kruskal-Wallis). Additionally, for mean comparisons, Tukey’s test at 5% was applied for parametric data, and Dunn’s test for non-parametric data. The results show that the physicochemical parameters varied and tended to increase with higher extract concentrations. Regarding acaricidal effects, T3, with a 6.43% concentration, showed the highest tick mortality, with an 88% efficiency at 12 hours and 98% at 48 hours. Furthermore, the aqueous extract maintained a prolonged residual effect at all concentrations up to 48 hours, at which point the maximum mortality rate was reached. The aqueous extract of yellow mamey proves to be an effective treatment for tick control under in vitro conditions, showing prolonged action and concentration-dependent efficacy.